2018
DOI: 10.1155/2018/4512924
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Optimization of Dual Threshold Independent-Gate FinFET and SRAM Cells

Abstract: Independent-Gate (IG) FinFET is a promising device in circuit applications due to its two separated gates, which can be used independently. In this paper, we proposed a comprehensive method to optimize the Dual Threshold (DT) IG FinFET devices by carrying out modulations for the gate electrode work function, oxide thickness, and silicon body thickness. Titanium nitride (TiNx) is used as the tunable work function gate electrode for good performances. The thicknesses of the gate oxide and silicon body are swept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The synthesis tools, such as commercial tools like Synopsys Design Compiler (DC), public-domain tools like ABC [8], and synthesis algorithms like factorizationbased methods, usually utilizing these single-gate standard cell libraries to optimize the circuit topology. However, according to our research, DTIG FinFET-based circuits have excellent performances and can be used in modern VLSI circuits [9][10][11]. So it has an emerging need to develop a comprehensive method based on DTIG FinFETs.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The synthesis tools, such as commercial tools like Synopsys Design Compiler (DC), public-domain tools like ABC [8], and synthesis algorithms like factorizationbased methods, usually utilizing these single-gate standard cell libraries to optimize the circuit topology. However, according to our research, DTIG FinFET-based circuits have excellent performances and can be used in modern VLSI circuits [9][10][11]. So it has an emerging need to develop a comprehensive method based on DTIG FinFETs.…”
Section: Introductionmentioning
confidence: 95%
“…Compared with single-gate devices, such as CMOS or CG FinFET, DTIG FinFET can design more flexible circuits by using of the low-threshold (low-V th ) and high-threshold (high-V th ) devices [2,3,9,11,20]. We have built a mini DTIG FinFET logic cells library for further using and as shown in Figure 1 are two examples and their CG comparisons.…”
Section: Dtig Finfet Cell Librarymentioning
confidence: 99%
“…In order to find ψ 1 , Eqs. ( 12), ( 13), (14), and ( 16) are combined to get…”
Section: Surface Potential Modelmentioning
confidence: 99%
“…Using MG-FinFETs, the width quantization effect on large circuits, such as SRAMs, can be reduced [11,12]. Also, in independent gate SRAMs, the dual gate system acts as a built-in feedback network and reduces read/write margins [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have shown that designing a circuit with devices with multiple input terminals is more flexible and efficient than using single-input ones [4,5]. The two-input low-threshold FinFET device proposed in the literature [6][7][8][9][10] is equivalent to two parallel transistors, while the two-input high-threshold FinFET device is equivalent to two series transistors. Therefore, the circuit can be simplified to reduce the transistor count by using two-input low-threshold and high-threshold FinFETs, thus reducing power consumption and the chip area.…”
Section: Introductionmentioning
confidence: 99%